The impact of domestic debt on economic growth in Zambia - Phiri, Kamphasa (Graduate School of Business (GSB), 2023)
Many developing countries like Zambia are faced with budgetary constraints. As a result, they bridge this gap in budgetary financing through borrowing. The borrowing is sometimes externally and can also be internally. Specifically, Zambia has gone through different phases as regards borrowing whether domestically or externally from the long ago. From the time Zambia received debt forgiveness there seems to be a rise again in the amount of debt that has been contracted both domestically and externally amidst falling growth in the economy. Therefore, this paper investigated the impact of Zambia's domestic debt on economic growth. To accomplish this, the debt-to-GDP ratio was used as a measure for domestic debt, while real GDP growth was used to gauge Zambia's economic growth from 1980 to 2018. The analysis was conducted using the Vector Error Correction model (VECM) and causality time series techniques. The results indicate that increased domestic borrowing led to a decline in Zambia's economic growth. Precisely, it was discovered that a 1% increase domestic debt resulted to a decrease (increase) of 0.988% in economic growth in the long run, holding all other factors constant. The Grander causality test shows that all variability does not cause economic growth. These results are further confirmed by the variance decomposition analysis. Based on the study findings the study makes the following recommendations. Firstly, the Zambian government should aim for lower levels of domestic borrowing that can be used for productive and efficient purposes. Secondly, to encourage faster growth, the real interest rate should be stable and real effective exchange rate can be improved through increased manufacturing, which results in increased exports. Lastly, governments can sell some parastatal companies to reduce large public expenditures while also increasing revenue, thereby boosting real GDP growth.